Respuesta :

(4.8 x 10^6)(3.6 x 10^3) / (2 x 10^5)

= (4.8 x 3.6) x 10^(6+3) / 2 x 10^5

= 17.28 x 10^9 / 2 x 10^5

= (17.28 / 2) x 10^(9 - 5)

= 8. 64 x 10^4

gmany

Scientific notation:

[tex]a\cdot10^k[/tex] where [tex]1\leq a < 10[/tex] and [tex]k\in\mathbb{Z}[/tex]

[tex]\dfrac{(4.8\cdot10^6)(3.6\cdot10^3)}{2\cdot10^5}[/tex]

use associstive and commutative property

[tex]=\dfrac{(4.8\cdot3.6)(10^6\cdot10^3)}{2\cdot10^5}[/tex]

use [tex]a^n\cdot a^m=a^{n+m}[/tex]

[tex]=\dfrac{17.28\cdot10^9}{2\cdot10^5}=\dfrac{17.28}{2}\cdot\dfrac{10^9}{10^5}[/tex]

use [tex]\dfrac{a^n}{a^m}=a^{n-m}[/tex]

[tex]=8.64\cdot10^4[/tex]

Answer:

[tex]\dfrac{(4.8\cdot10^6)(3.6\cdot10^3)}{2\cdot10^5}=8.64\cdot10^4[/tex]

ACCESS MORE